2010
DOI: 10.3109/00365521003793741
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic duct changes are not associated with early signs of chronic pancreatitis at magnetic resonance imaging (MRI) in patients with primary sclerosing cholangitis

Abstract: Pancreatic duct changes are associated with extrahepatic bile duct strictures and not with the early MRI signs of CP. Therefore, pancreatic duct changes seem to be part of the spectrum of PSC and should not be defined as CP. Pancreatic duct changes are of limited clinical importance but may contribute to abdominal pain in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A clinical observation is that PSC patients seem to develop PEP more often than other patients undergoing ERCP and a high frequency of PEP has previously been reported . Disease involvement of the pancreatic duct in PSC is reported to be present in 24% of all PSC patients . We therefore hypothesize that PSC is a risk factor for PEP.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…A clinical observation is that PSC patients seem to develop PEP more often than other patients undergoing ERCP and a high frequency of PEP has previously been reported . Disease involvement of the pancreatic duct in PSC is reported to be present in 24% of all PSC patients . We therefore hypothesize that PSC is a risk factor for PEP.…”
mentioning
confidence: 75%
“…The reason why patients with PSC have an increased risk for PEP is unknown. The pancreatic duct in some PSC patients is affected by sclerotic disease and early signs of pancreatic changes at magnetic resonance imaging (MRI) are found in high frequency in patients with PSC . The pancreas in PSC may therefore be affected by an inflammatory attack, which over time may cause sclerosis, similar to the disease progression seen in the bile ducts.…”
Section: Discussionmentioning
confidence: 99%
“…59 Little research exists on pancreatic changes in patients with PSC, especially in PSC-IBD patients. Said et al 60 studied 103 PSC patients, 76% with concomitant IBD, and found that 24% of PSC patients had pancreatic ductal changes (side branch or main pancreatic duct (MPD) dilatation) diagnosed by magnetic resonance cholangiopancreatography. None of the patients had typical imaging features of AIP and only one patient had clinical and laboratory findings diagnostic of CP.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…The resultant pancreatic inflammation may be too intermittent or mild to cause clinically overt pancreatitis, but the chronic mild inflammation may be pro-neoplastic. In one study of 103 patients with PSC, 24% of the patients had pancreatic duct changes, which were associated with duration of disease and extrahepatic biliary involvement ( 20 ). Additionally, PSC may possibly affect pancreatic ductal cells directly - not as dramatically as to cause the same “beads on a string” appearance as is seen on a cholangiogram - but enough to cause chronic mild inflammation.…”
Section: Discussionmentioning
confidence: 99%